Crystal Methamphetamine Injection Predicts Slower HIV RNA Suppression among Injection Drug Users - Fairbairn, Nadia (2011)
We examined the impact of crystal methamphetamine injection on HIV RNA suppression among a prospective cohort of HIV-positive injection drug users initiating antiretroviral therapy. A multivariate Cox regression analysis found crystal methamphetamine injection to be negatively associated with viral load suppression (RH = 0.63 [95% CI: 0.40 – 0.98]; p = 0.039). This study is the first to our knowledge to demonstrate an association between crystal methamphetamine use and HIV RNA suppression.